Interactive digital television technologies and applications - Lekakos 1968- (IGIPub., 2008)
"This book presents developments in the domain of interactive digital television covering both technical and business aspects. It focuses on analyzing concepts, research issues, and methodological approaches, analyzing existing solutions such as systems and prototypes for researchers, academicians, scholars, professionals and practitioners"--Provided by publisher.